Prognostic Comparison Between Liver Resection and Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma Patients With Bile Duct Tumor Thrombus: A Propensity-Score Matching Analysis - Liu, Zong-Han; Sun, Ju-Xian; Feng, Jin-Kai; Yang, Shi-Ye; Chen, Zhen-Hua; Liu, Chang; Chai, Zong-Tao; Mao, Fei-Fei; Guo, Wei-Xing; Shi, Jie; Cheng, Shu-Qun (Frontiers in Oncology, 2022)
Abstract Background: Hepatocellular carcinoma (HCC) with bile duct tumor thrombus (BDTT) is rare. The aim of this study is to evaluate the long-term prognosis of liver resection (LR) versus transcatheter arterial chemoembolization (TACE) in these patients. Methods: Data from HCC patients with BDTT who underwent liver resection and TACE were analyzed respectively. Propensity score matching (PSM) analysis was performed in these patients. Results:145 HCC patients with BDTT were divided into two groups: the LR group (n=105) and the TACE group (n=40). The median OS in the LR group was 8.0 months longer than that in the TACE group before PSM (21.0 vs. 13.0 months, P<0.001) and 9.0 months longer after PSM (20.0 vs. 11.0 months, P<0.001). The median DFS in the LR group was 3.5 months longer than that in the TACE group before PSM (7.0 vs. 3.5 months, P=0.007) and 5 months longer after PSM (7.0 vs. 2.0 months, P=0.007). Conclusion: If surgery is technically feasible, liver resection provides better prognosis for HCC patients with BDTT compared with TACE.